Genomic diversity and evolutionary dynamics of Influenza A viruses in Colombian swine: implications for one health surveillance and control - Karl Ciuoderis; Jaime Usuga; Laura S. Pérez-Restrepo; Manuel Gonzalez-Ramirez; Leidi Carvajal; Andrés Cardona; Isabel Moreno; Andrés Diaz; Mario Peña; Juan P. Hernández-Ortiz; Jorge E. Osorio (Emerging Microbes and Infections)
Influenza A viruses (IAV) impose significant respiratory disease burdens in both swine and humans worldwide, with frequent human-to-swine transmission driving viral evolution in pigs and highlighting the risk at the animal-human interface. Therefore, a comprehensive One Health approach (interconnection among human, animal, and environmental health) is needed for IAV prevention, control, and response. Animal influenza genomic surveillance remains limited in many Latin American countries, including Colombia. To address this gap, we genetically characterized 170 swine specimens from Colombia (2011–2017). Whole genome sequencing revealed a predominance of pandemic-like H1N1 lineage, with a minority belonging to H3N2 and H1N2 human seasonal-like lineage and H1N1 early classical swine lineages. Significantly, we have identified reassortant and recombinant viruses (H3N2, H1N1) not previously reported in Colombia. This suggests a broad genotypic viral diversity, likely resulting from reassortment between classical endemic viruses and new introductions established in Colombia's swine population (e.g. the 2009 H1N1 pandemic). Our study highlights the importance of a One Health approach in disease control, particularly in an ecosystem where humans are a main source of IAV to swine populations, and emphasizes the need for continued surveillance and enhanced biosecurity measures. The co-circulation of multiple subtypes in regions with high swine density facilitates viral exchange, underscoring the importance of monitoring viral evolution to inform vaccine selection and public health policies locally and globally.